Energy Consumption and Life Cycle Costs of Overhead Catenary Heavy-Duty Trucks for Long-Haul Transportation - Ivan Mareev (Energies, 2018)
The overhead catenary truck is an interesting technology for long-haul transportation with heavy-duty trucks because it can combine the advantage of energy supply via catenary while driving and the flexibility of a battery truck on routes without catenary using the traction battery. This study investigates the energy consumptions of overhead catenary trucks on German highways and considers different configurations for the traction battery and catenary power system. Afterwards the life cycle costs of overhead catenary trucks are calculated for a specified long-haul transportation scenario and the results are compared to battery electric truck and diesel truck using the findings of a previous study by the authors. The energy consumption of the considered overhead catenary trucks is approximately equal to that of a battery electric truck but only about a half of the equivalent energy consumption of a conventional diesel truck. According to the cost assumptions in this study, the total life cycle costs of overhead catenary trucks can be in the range of the conventional diesel truck, showing the competitiveness of this alternative truck technology.